Assisted natural regeneration of selected tree species through silviculture interventions as a tool for restoring degraded natural forests in northwestern Ethiopia - Melkamu Kassaye; Amsalu Nigatu; Bahiru Gedamu; Yonas Derebe; Mulugeta Tamer; Fentahun Ayne; Etsegenet Emiru; Beyene Belay (Forest Science and Technology, 2023)
AbstractNatural forest ecosystem assets and services are increasingly deteriorating due to forest degradation and deforestation in Northern parts of Ethiopia. Enhancing the natural regeneration status of native tree species through different silviculture practices is highly Forest regeneration method recommended. Thus, this study aims to investigate the role of different silvicultural interventions in enhancing the regeneration condition of selected ecological and economical important tree species. Three natural forests stands from different agro-ecologies were chosen and three silvicultural treatments including Fencing, Fence + hoeing, Fence + gap creation, and control (without any intervention) with 400 m2 plot areas established with three replications and randomized complete block design (RCBD) with a total of 36 plots. In each plot, seedling, and saplings under different mod of regeneration were recorded while height and diameter at breast height were measured and analyzed using descriptive and inferential statistics using R version 4.1. There was a significant difference (p < .05) in seedling density and regeneration status among forest stands, methods of regeneration, silvicultural methods, and season of regeneration. The Camboo forest stand recorded the highest regeneration (971 seedlings ha−1); seedlings regenerated from seed recorded the highest regeneration (368 seedlings ha−1), fencing and gap creation silvicultural intervention recorded the highest seedlings (961 seedlings ha−1), the highest regeneration density was recorded at mid-rainy season (570 seedlings ha−1); and Prunus africana and Albizia gummifera have the best regeneration capacity (245 seedlings ha−1) in the study forest stand. The regeneration status of trees under fencing and gap creation plots changed from J-shape to an inverted J-shape before and after silviculture intervention, respectively. The regeneration and population structure of many studied tree species showed particularly good condition in fenced plots than control plots which shows future management interventions for the restoration of degraded natural forest ecosystems in Ethiopia’s tropical forest ecosystems. Some native tree species, such as Hagenia abyssinica, Apodytes dimidata, and Ekebrgia capensis, have a weak response to silvicultural treatments that require advanced regeneration techniques such as clonal nurseries and invitro propagation.